2014
DOI: 10.3892/ol.2014.2016
|View full text |Cite
|
Sign up to set email alerts
|

Plasma vascular endothelial growth factor 165 in advanced non-small cell lung cancer

Abstract: Currently, there is no serum marker that is routinely recommended for lung cancer. Therefore, the aim of the present study was to demonstrate that plasma vascular endothelial growth factor 165 (VEGF 165) may be a potential marker for advanced lung cancer. Lung cancer is the leading cause of cancer-related mortality worldwide, therefore, it is important to develop novel diagnostic techniques. The present prospective case control study included two groups of patients; a control group of healthy volunteers and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…2b). Thus, concomitant COPD reduced G-MDSC-s and inverted the effect of VEGF on M-MDSC-s, which have been known to exert both proinflammatory and immunosuppressive effects in NSCLC [21,33]. There was no relationship between serum VEGF and G-MDSC-s in either groups.…”
Section: Vegf and Mdsc-smentioning
confidence: 79%
“…2b). Thus, concomitant COPD reduced G-MDSC-s and inverted the effect of VEGF on M-MDSC-s, which have been known to exert both proinflammatory and immunosuppressive effects in NSCLC [21,33]. There was no relationship between serum VEGF and G-MDSC-s in either groups.…”
Section: Vegf and Mdsc-smentioning
confidence: 79%
“…Preclinical and clinical studies have shown the important roles of VEGF‐A and VEGF‐C in LNM in solid cancers . Based on the hypothesis that the changes in the level of these growth factors in the tumor may be associated with parallel measurable changes in the peripheral blood circulation, there have been trials of measurements of the serum VEGF family for the diagnosis of several types of solid cancers including PTC . The use of circulating biomarkers is expected to be helpful to increase the diagnostic accuracy for identifying the metastatic status of PTC with minimal morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in the level of these angiogenesis factors in the tumor may be associated with parallel measurable changes in the peripheral blood circulation. The use of circulating biomarkers to identify cancer and to predict the prognosis of cancer patients appears to be helpful in some cancer types [13, 14]. However, whether serum angiogenetic factors can be used to diagnose local–regional neck or distant metastases and to predict the prognosis of patients with DTC is still unclear.…”
Section: Introductionmentioning
confidence: 99%